Increased platelet sensitivity among individuals with aspirin resistance – Platelet aggregation to submaximal concentration of arachidonic acid predicts response to antiplatelet therapy - Guthikonda, Sasidhar; Mangalpally, Kirankumar; Vaduganathan, Muthiah; Patel, Rajnikant; DeLao, Timothy; Bergeron, Angela L.; Dong, Jing-Fei; Lev, Eli I.; Kleiman, Neal S. (Thrombosis and Haemostasis, 2008)
Aspirin ‘resistance’ (AR) is a phenomenon of uncertain etiology describing decreased platelet inhibition by aspirin. We studied whether (i) platelets inAR demonstrate increased basal sensitivity to a lower degree of stimulation and (ii) platelet aggregation with submaximal stimulation could predict responses to aspirin. Serum thromboxane B2 (TxB2) levels and platelet aggregation with light transmission aggregometry (LTA ) were measured at baseline and 24 hours after 325 mg aspirin administration in 58 healthy subjects. AR was defined as the upper sixth of LTA (≥ 12%) to 1.5 mM AA. Baseline platelet aggregation with sub-maximal concentrations of agonists [ADP 2 µM, arachidonic acid (AA) 0.75 mM, collagen 0.375 and 0.5 µg/ml] was greater in AR subjects compared with non-AR subjects, but not with higher concentrations (ADP 5 µM and 20 µM, AA 1.5 mM and collagen 1 µg/ml). Post-aspirin platelet aggregation was elevated in AR subjects with both submaximal and maximal stimulation. Baseline and post-aspirin serumTxB2 were higher inAR subjects and decreased further with ex-vivo COX -1 inhibition, suggesting incompletely suppressed COX -1 activity. Pre-aspirin platelet aggregation to 0.75 AA demonstrated a dichotomous response with 29/58 subjects having aggregation ≤15% and 29/58 subjects having aggregation ≥75%. In the high aggregation group 28% had AR compared to 6% in the non-AR group (p=0.04). In conclusion, platelets in AR subjects demonstrate increased basal sensitivity to submaximal stimulation, which could predict responses to antiplatelet therapy.
Keywords: Platelets; aspirin resistance; thromboxane